The Impact of Investment in AI on Bank Performance: Empirical Evidence from Pakistan's Banking Sector (KASBIT Business Journal, 2024)
Artificial Intelligence has gain attention of researcher, owners and investors because it plays a vital role in the success of any type of business (Small and medium enterprises to large level). So the purpose of this study is to investigate the impact of artificial intelligence investment on bank performance. Little research considered the relationship between these variables. Data are collected from annual reports of 18 banks available on Pakistan Stock Exchange. Study period is from 2011-2022 and total observation of this study is 216. In this study we used event study methodology for AI and quantitative measures for bank performance. Bank Performance are measured through these proxies i.e. Net profit margin, Return on Equity, and Return on Assets. Control variable used in this study are Bank Size, and Bank Age. Results shows that artificial intelligence investment positively contribute into bank performance. This study has implications for stakeholders especially for owners of banks to focuses on artificial intelligence to increases bank performance. This study presents pioneering empirical evidence regarding artificial intelligence's impact on bank performance. It also serves as a valuable reference for business considering artificial intelligence investments.
Keywords: Artificial Intelligence investment; Bank performance; Pakistan Stock Exchange; Emerging market; Pakistan